THE EFFECT OF TEACHERS’ DIRECT AND INDIRECT FEEDBACK ON STUDENT’ S WRITING ABILITY - Yuli Latifah; Bambang Suwarno; Irma Diani (JOALL (Journal of Applied Linguistics and Literature), 2018)
This study is intended to find out any difference in effectiveness between direct and indirect feedback on students’ writing ability. The design was Quasi-Experiment. The population consisted of the students of the X class of SeniorHigh School 4, Rejang Lebong, Curup, Indonesia. The samples comprised 32 students in group 1 and 32 Students in group 2. The instrument was a writing test. In the data analysis, the researcher used the normality, homogeneity,and t-test.These were calculated and analyzed by using SPSS 20. The tests consisted of pre-test and post-test. In post-test, there was no significant difference between groups on all aspect. There were two results of this study.Firstly, in the post test there was a difference of mean score between experiment group 1 and experiment group 2. In general ability, in group 1 increased by 15.59. Meanwhile, the group 2 increased by 2.60. This indicated that there was an effect of indirect feedback on students’ writing ability. From t-test calculation, t-count was 3.274 which t-table was 1.670. It showed that t obtained was bigger than t-table (3.274 > 1.670). H0 was rejected and H1 was accepted. In other words, the indirect feedback technique was effective on students’ wri ting ability. Based on the data analysis, the indirect feedback technique was positively effective in increasing on students’ writing ability, on general writing ability. There were also significant differences between both groups in the writing ability aspects such as organization, language use and vocabulary.